DevelopmeTHE APPLICATION OF AUGMENTED REALITY TECHNOLOGY TO SUPPORT LEARNING FOR STUDENTS WITH HEARING IMPAIRMENTSnt of Augmented Reality Technology to Support Science Learning for Children with Hearing Impairments - Sudthongkhong, Chudanat; Phattharachairawee, Thanannath; Soontornpipit, Pichitpong; Soermphongsuwar, Amnaj (Journal of MCU Nakhondhat, 2025)
The application of augmented reality (AR) technology to develop instructional media for learners with hearing impairments focuses on designing materials that integrate images, videos, captions, and sign language to enhance accessibility and diversify learning formats. Deaf learners often experience difficulties accessing information from traditional instructional media, which typically lack interactivity and consequently slow down the learning process. The use of supplementary programs and media, such as AR books and three-dimensional models linked to the lessons, helps reduce communication barriers and creates learning experiences that facilitate understanding and provide opportunities for learning on an equal footing with hearing peers. The learning process is further supported by Playful Learning Innovation, which emphasizes play-based and participatory learning, constructivist principles, whereby learners actively construct knowledge through direct experience, multimedia learning, which integrates images, text, and video; as well as experiential learning and Universal Design for Learning (UDL), which highlight diversity in the modes of representation, engagement, and expression. Moreover, the use of AR technology in learning enables students with hearing impairments to explore three-dimensional models, rotate, zoom in and out, and interact with the information engagingly. Textual descriptions and sign language can also be incorporated to further enhance comprehension for learners with hearing impairments. Integrating AR technology plays a crucial role in supporting the understanding of complex content, making abstract concepts easier for students to grasp, enhancing motivation and engagement, and improving academic achievement, particularly in science subjects, as evidenced by case study findings. And can learn at a level comparable to hearing students, reflecting the potential of augmented reality technology to help reduce educational inequities.